A smart voltage protection system using GSM - Md. Mehedi Rahman Khan (Journal of Emerging Innovations in Engineering, 2025)
Automation in the power distribution field permits utilities on actualize all the adaptable control for power distribution systems, which can be used to optimize efficiency, reliability, quality of electric service. Automation not only upgrade those qualities but also reduces human effort and saves time. Over and under voltage problem is a common type of problems which leads to most of the insulation and appliance damage throughout in any country. In this paper we are introducing to an Arduino based automation system with a GSM module to protect over and under voltage problem using SMS alert and real time monitoring in power distribution system.